Mengapa Ipv6 Gagal ? - Dedy Syamsuar (Jurnal Sistem Informasi, 2018)
ABSTRACTIPv6 was introduced to replace IPv4 as the main IP address. However, despite being more than 15 years since itsstandardization, IPv6 failed to achieve any meaningful diffusion through the Internet. While previous researchhas debated, discussed and explored the IPv6 adoption, this study provides a theoretical perspective to investigatethe failure of IPv6 to diffuse from resistance perspective. Drawing on Tornatzky and Fleischer’s TOE (Technology-Organization-Environment) framework and integrating prior adoption and resistance literatures, we propose amodel of IPv6 resistance. The antecedents of the proposed model basically represent three dimensions of TOEframework including Technological context (lack of need, satisfaction with current system, switching cost andperceived of threat), Organizational context (resource barrier and IT sophistication) and Environmental context(regulatory support). Furthermore, the model can be used to explore and recognize why most of organization asend user still resist over the IPv6.Keywords: IPv6, resistance technology, adoption technologyABSTRAKIPv6 diperkenalkan untuk menggantikan IPv4 sebagai protocol pengalamatan utama di Internet. Tetapi meskipuntelah lebih dari 15 tahun ditetapkan sebagai standard, IPv6 gagal mencapai difusi yang berarti. Sementarapenelitian sebelumnya telah memperdebatkan, membahas dan mengeksplorasi adopsi IPv6, penelitian inimemberikan perspektif teoritis untuk menyelidiki kegagalan IPv6 untuk menyebar dari perspektif resistansi.Menggunakan kerangka kerja Tornatzky & Fleischer's TOE (Technology-Organization-Environment) danintegrasi dengan literatur adopsi dan resistensi sebelumnya, kami mengusulkan sebuah model resistensi IPv6.Antescedent dari model yang diusulkan pada dasarnya mewakili tiga dimensi kerangka TOE termasuk konteksTeknologi (lack of need, satisfaction with current system, switching cost and perceived of threat), konteksorganisasi ((resource barrier and IT sophistication) dan konteks lingkungan (regulatory support). Selanjutnya,model tersebut dapat digunakan untuk mengeksplorasi dan mengenali mengapa sebagian besar organisasi masihmenolak IPv6.Keywords: IPv6, penolakan teknologi, adopsi teknologi